2022
DOI: 10.3390/ijerph19137772
|View full text |Cite
|
Sign up to set email alerts
|

Race, Zoonoses and Animal Assisted Interventions in Pediatric Cancer

Abstract: Emerging evidence accumulates regarding the benefits of animal-assisted interventions (AAIs) in facilitating pediatric cancer treatment and alleviating symptomatology through positive changes in the patients’ emotional, mental, and even physical status. A major concern expressed by healthcare providers and parents in implementing AAIs in hospital settings is the transmission of disease from animals to patients. Immunocompromised children, such as pediatric cancer patients are at increased risk for pet-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Although substantial benefits have been documented in the literature on the involvement of dogs in AAI, physical contact between humans and animals could cause the carrying of potential pathogens from animals to human beings. Sometimes, in AAI settings the dogs employed might also represent pathogen carriers causing a pathogen exchange from being contaminated by physical contact with infected/haunted subjects and then transferring microorganisms to other patients [2,52]. In particular, it is scientifically demonstrated that pediatric oncological patients have immunodeficiency cancer treatments mediated and therefore are retained to be more susceptible [2,47].…”
Section: Potential Zoonoses Associated With Dogsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although substantial benefits have been documented in the literature on the involvement of dogs in AAI, physical contact between humans and animals could cause the carrying of potential pathogens from animals to human beings. Sometimes, in AAI settings the dogs employed might also represent pathogen carriers causing a pathogen exchange from being contaminated by physical contact with infected/haunted subjects and then transferring microorganisms to other patients [2,52]. In particular, it is scientifically demonstrated that pediatric oncological patients have immunodeficiency cancer treatments mediated and therefore are retained to be more susceptible [2,47].…”
Section: Potential Zoonoses Associated With Dogsmentioning
confidence: 99%
“…Sometimes, in AAI settings the dogs employed might also represent pathogen carriers causing a pathogen exchange from being contaminated by physical contact with infected/haunted subjects and then transferring microorganisms to other patients [2,52]. In particular, it is scientifically demonstrated that pediatric oncological patients have immunodeficiency cancer treatments mediated and therefore are retained to be more susceptible [2,47]. The modes of pathogens transmission can include physical interaction, aerosol inhalation, infected saliva, urine, or feces, as well as contact with contaminated tools [53].…”
Section: Potential Zoonoses Associated With Dogsmentioning
confidence: 99%
See 3 more Smart Citations